Experimental Study: Coloring Activities with the Abur Wipe Technique as a Means of Early Childhood Fine Motor Development - Marliyastuti, Novia; Ardina, Mona; Fitriana, Septi (CV Media Inti Teknologi, 2024)
The purpose of this study is to ascertain how coloring activities using the Abur wipe technique affect young children's fine motor abilities. The study design is quasi-experimental design, quantitative research with an experimental approach. The study's population consisted of 11 pupils from Pamardi Siwi Kindergarten and 13 students from Pangudi Luhur Kindergarten who belonged to group A. Total sampling approach was employed in the sampling process. Methods for gathering data through testing. According to the findings, group A children in the experimental class had an average value of fine motor skills that was 88.36 points greater than the control class's average value of 74.15. The significant value of 0.000 < 0.05 indicates that the abur wipe technique has an impact on the fine motor abilities of kindergarten students in group A, according to the findings of the hypothesis test.